Breaking Barriers in OCD Treatment: A Resistant Case Successfully Treated with an Innovative Exposure and Response Prevention Strategy - Dhankar, Abhinav; Kumar, kunal; Kumar, Abhinit; Nayar, Nikhil; Goyal, Ayushi; Jain, Soumya; Agrawal, Shlok (Journal of Neonatal Surgery, 2025)
It is widely recognized that the most effective approach to treating obsessive-compulsive disorder (OCD) combines medication with cognitive-behavioral therapy (CBT), particularly exposure and response prevention (ERP). This case sheds light on a unique and unconventional way of applying ERP in a patient with treatment-resistant and atypical OCD, ultimately proving more beneficial than medication alone. What made this case unusual was the patient’s deeply ingrained overvalued ideas, superstitions, and strong religious beliefs, which played a significant role in shaping their symptoms. Additionally, the patient tended to misinterpret random events as meaningful, experienced heightened stimulus generalization, and responded best to in vivo exposure, making their treatment journey both challenging and distinct.